Report of the Hospital Sub-committee - Horder, Thomas, 1871-1955 (London : Institutional Management Association)
1943-09-11 1943 1940s 15 pages APPENDIX. In the planning of new hospital accommodation or in the adaptation and modernisation of older buildings, it is hoped that the suggestions put forward in this appendix will be given consideration. 1. Living Accommodation. The premises should have central heating and modem lighting throughout and be equipped with facilities for the use of modern equipment. Public telephones should be installed in adequate numbers and in convenient positions for the use of the staff. 2. Private Rooms. Bedrooms, bedsitting rooms, and private sitting rooms are the rooms in which the resident members of the domestic staff spend a good deal of their leisure, and most of their non-working hours. The whole of their working life is spent in communal surroundings, and they do not, as in the case of the non-resident workers, get away to home conditions and a different atmosphere. The quality of the accommodation, therefore, plays an important part in the happiness of the staff, and influences to no small extent the decision to settle down to a life in hospital. No effort should be spared to ensure good planning, and attention to detail in plans, furniture and equipment, so that the living quarters may be both comfortable and attractive. Private rooms should be adequate in size for their purpose and preferably not all of one shape. Where possible the outlook should be good. They should be quiet, light and well-ventilated. There should be suitably placed artificial lighting, with two-way switches for convenience and economy. Colour schemes should be attractive, and should be such that newcomers' possessions can harmonize with them. All private rooms should have at least one drawer and cupboard made to lock. For economy of construction the chest-of-drawers can be made with long drawers only, the top one having two or three partitions. For staff who have no personal sitting room it is recommended that divan beds be used. Washing accommodation should be either completely enclosed or a washing cubicle should be provided outside the room. Sufficient bathroom accommodation should be provided both for trained staff and for maids. The Domestic Administrator should have a private bathroom. In all private rooms for staff there should be provision for plugs for wireless. One of the difficulties encountered when trying to provide pleasant and attractive rooms for the resident staff is due to the fact that the small wear and tear marks such as stains of ink, acid, cosmetics, and other liquids, the marks of pictures on the walls, etc., make a room unattractive to the newcomer. It is, therefore, advisable to have wall and paint coverings which can easily be renewed or touched up and to have soft furnishings which will wash and repair easily. All hard surfaces such as table, bureau and dressing table tops should be treated to prevent staining. This can be effected by the use of plate glass or by painting the wood with a stain resisting finish. 11 292/842/2/104